2013
DOI: 10.1097/bpo.0b013e3182745456
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Differences in Adolescent-diagnosed and Adult-diagnosed Acetabular Dysplasia Compared With Infantile Developmental Dysplasia of the Hip

Abstract: Infantile DDH is diagnosed with neonatal examination and patients are routinely followed into adolescence. Adolescent/adult AD is not detected until symptoms develop. Further study is needed to determine whether younger family members of patients with hip osteoarthritis should be screened to detect potentially at-risk hips.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 18 publications
2
47
2
Order By: Relevance
“…This latitudinal difference has also been noted in children with Perthes' disease [58]. Within DDH there are two different types, the typical infantile DDH and the late onset adolescent/adult acetabular dysplasia [59]. The older group, when compared to the infantile group, demonstrated a lower female predominance (88.0 versus 98.0%) with more bilateral involvement (61.2% versus 45.1%).…”
Section: Discussionmentioning
confidence: 68%
“…This latitudinal difference has also been noted in children with Perthes' disease [58]. Within DDH there are two different types, the typical infantile DDH and the late onset adolescent/adult acetabular dysplasia [59]. The older group, when compared to the infantile group, demonstrated a lower female predominance (88.0 versus 98.0%) with more bilateral involvement (61.2% versus 45.1%).…”
Section: Discussionmentioning
confidence: 68%
“…Engesaeter et al [18] also reported that, unexpectedly, only 8 % of those who underwent THR due to dysplasia were reported to have had unstable hips at birth. Lee et al [19] concluded that in 209 of 311 patients who underwent periacetabular osteotomy, acetabular dysplasia had not been diagnosed before adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Breech position, family history, female gender, oligohydramnios, congenital anomalies, and primiparity were considered to be risk factors. Evidence, however, is valid for positive family history only in first-degree family members [19]. …”
Section: Discussionmentioning
confidence: 99%
“…More than 75% of patients with FAI can have bilateral deformity [2,4] and 61% to 84% of patients with acetabular dysplasia have signs of dysplasia in the contralateral hip [11,13]. Inclusion of bilateral hips in any population study may therefore overestimate the prevalence of the deformity of interest.…”
Section: Where Do We Need To Go?mentioning
confidence: 96%